Theoretical conceptions of editorial processes in scientific journals from a regulatory approach - Molinet Rojas, Grabiel; Linares Herrera, Manuel Paulino; Fernández Hernández, Carlos (Advanced Notes in Information Science, 2022)
Technological evolution based on information and communication has been present in this process of constitution of scientific communication. Promotion actions are required for a better integration of the journals in the national and international scientific community, and in society in general. For these, stipulated plans are suggested from the university management. Work procedures are required in a regulated, regulated and collegiate manner so that the sponsoring entities and the publisher are part of the work procedures and participate in decision-making. Discussions on the proposed guidelines may be useful in the creation and implementation of internal and external communication strategies of scientific journals that contribute to the improvement of editorial production processes.